Hydrogen sulfide pretreatment improves mitochondrial function in myocardial hypertrophy via a SIRT3‐dependent manner - Meng, Guoliang (Br J Pharmacol, 2017)
BACKGROUND AND PURPOSE: Hydrogen sulfide (H(2)S) is a gaseous signal molecule with antioxidative properties. Sirtuin 3 (SIRT3) is closely associated with mitochondrial function and oxidative stress. The study was to investigate whether and how H(2)S improved myocardial hypertrophy via a SIRT3‐dependent manner. EXPERIMENTAL APPROACH: Neonatal rat cardiomyocytes were pretreated with NaHS (50 μM) for 4 h followed by angiotensin II (Ang II, 100 nM) for 24 h. SIRT3 was silenced with siRNA technology. SIRT3 promoter activity and expression, cell surface, hypertrophic gene mRNA expression, mitochondrial oxygen consumption rate and membrane potential were measured. Male 129S1/SvImJ [wild‐type (WT)] and SIRT3 knockout (KO) mice were injected with NaHS (50 μmol·kg(−1)·day(−1); i.p.) followed by transverse aortic constriction (TAC). Echocardiography, heart mass, mitochondrial ultrastructure, volume and number, oxidative stress, mitochondria fusion and fission‐related protein expression were measured. KEY RESULTS: In vitro, NaHS increased SIRT3 promoter activity and SIRT3 expression in Ang II‐induced cardiomyocyte hypertrophy. SIRT3 silencing abolished the ability of NaHS to reverse the Ang II‐induced cardiomyocyte hypertrophy, mitochondrial function impairment and permeability potential dysfunction, along with the decline in FOXO3a and SOD2 expression. In vivo, after TAC. NaHS attenuated myocardial hypertrophy, inhibited oxidative stress, improved mitochondrial ultrastructure, suppressed mitochondrial volume but increased mitochondrial numbers, enhanced OPA1, MFN1 and MFN2 expression but suppressed DRP1 and FIS1 expression in WT mice but not in SIRT3 KO mice CONCLUSION AND IMPLICATIONS: NaHS improved mitochondrial function and inhibited oxidative stress in myocardial hypertrophy in a SIRT3‐dependent manner. LINKED ARTICLES: This article is part of a themed section on Spotlight on Small Molecules in Cardiovascular Diseases. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.8/issuetoc